The Influence of Zakat, Infaq, Sadaqah, Sukuk, and Islamic Financing on Economic Growth in Indonesia for the 2011-2024 Period - Khalid Miftahuda; Galuh, Ajeng Kartika (Islamic Economics and finance in Focus, 2025)
This study aims to investigate the influence of zakat, infaq, shadaqah (ZIS), sukuk, and Islamic financing on Indonesia's Gross Domestic Product (GDP). This research employs a quantitative approach. Research samples were collected from official government literature, namely the Central Statistics Agency (BPS), the Financial Services Authority (OJK), and the National Amil Zakat Agency (BAZNAS). The data analysis technique used in this study is the Vector Error Correction Model (VECM), implemented with EViews software. The research results indicate that ZIS affects economic growth in Indonesia in the short term due to the influence of income distribution, which increases the consumption of the poor, thereby affecting aggregate demand, and this aligns with Keynesian theory. Furthermore, Islamic financing affects economic growth in Indonesia in the short term because the dominant contract used is murabahah. However, sukuk and inflation do not affect economic growth in Indonesia. For future research, it is suggested to conduct comparative studies with other countries to understand the influence of Islamic economic variables more contextually. For the government, it is hoped that policies can be issued to maximize sharia economic instrument funds so that they can provide maximum benefits to the Indonesian people.